2021
DOI: 10.4012/dmj.2019-324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poly (γ-glutamic acid)/tricalcium phosphate (γ-PGA/TCP) composite for dentin remineralization <i>in vitro </i>

Abstract: The poly (γ-glutamic acid)/tricalcium phosphate (γ-PGA/TCP) composite was fabricated as a novel biomineralization material function in preventing caries. Demineralized bovine dentin specimens were prepared and randomly divided into 5 groups (i. α-TCP, ⅱ. γ-PGA, ⅲ. γ-PGA/TCP, ⅳ. CPP-ACP, and ⅴ. deionized water) and subjected to 14 days of pH cycling. Remineralization ability was evaluated by lesion depth, mineral loss and microhardness. The morphology of dentin depositions was observed with scanning electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This result may be due to the adhesion of C. albicans on the bovine dentin surface influencing the surface roughness; the detection of surface roughness by CLSM can be easily affected by the environment, which could have led to the lack of a significant difference between the two groups. SEM images showed that the bovine dentin surface morphology of the S. mutans MV-treated group had more dentin tubule exposure and broken dentin tubules, indicating the erosion of peritubular dentin and consistent with previous research reports ( Poggio et al., 2013 ; Su et al., 2021 ). Altogether, these findings provide evidence that S. mutans MVs increase bovine dentin demineralization provoked by C. albicans biofilms.…”
Section: Discussionsupporting
confidence: 91%
“…This result may be due to the adhesion of C. albicans on the bovine dentin surface influencing the surface roughness; the detection of surface roughness by CLSM can be easily affected by the environment, which could have led to the lack of a significant difference between the two groups. SEM images showed that the bovine dentin surface morphology of the S. mutans MV-treated group had more dentin tubule exposure and broken dentin tubules, indicating the erosion of peritubular dentin and consistent with previous research reports ( Poggio et al., 2013 ; Su et al., 2021 ). Altogether, these findings provide evidence that S. mutans MVs increase bovine dentin demineralization provoked by C. albicans biofilms.…”
Section: Discussionsupporting
confidence: 91%
“…S. Vyavhare et al reported a similar trend for comparing different remineralizing agents on surface microhardness recovery. The reported SMHR% for nano-HAp (10%), CPP-ACP (10%), NaF (1000 ppm), and deionized water (negative control) after 6 days of pH cycling were 37.06 ± 7.32%, 18.17 ± 7.70%, 37.68 ± 7.06%, and 16.52 ± 8.77%, respectively [ 53 ]. Furthermore, γ-PGA/tricalcium phosphate was recently reported to be more effective than CPP-ACP at enhancing the microhardness of bovine dentin samples after 2 weeks of pH cycling remineralization [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reported SMHR% for nano-HAp (10%), CPP-ACP (10%), NaF (1000 ppm), and deionized water (negative control) after 6 days of pH cycling were 37.06 ± 7.32%, 18.17 ± 7.70%, 37.68 ± 7.06%, and 16.52 ± 8.77%, respectively [ 53 ]. Furthermore, γ-PGA/tricalcium phosphate was recently reported to be more effective than CPP-ACP at enhancing the microhardness of bovine dentin samples after 2 weeks of pH cycling remineralization [ 53 ]. S. Huang et al reported 35.4% of SMHR in 144 min of treatment time in enamel remineralization under the pH-cycling model for dental caries, using nano-HAp combined with Galla chinensis (GCE) [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that charged groups in collagen provide nucleation sites for inducing apatite nucleation. The experimental results of Su et al (2021) suggested that type I collagen has a complex and ordered structure and plays a positive role in guiding the penetration of minerals into nucleation. Nevertheless, whether collagen alone can form intrafibrillar mineralization remains controversial.…”
Section: Importance Of Collagen In Biomineralizationmentioning
confidence: 99%